New potato variety Virazh with resistance to golden potato nematode - Z. F. Serqeeva; N. F. Sintsova; M. Yu. Merkusheva; I. V. Lyskova (Аграрная наука Евро-Северо-Востока, 2016)
Characteristics of mid-early potato variety Virazh (Gloriya x 282-97) which combines high productivity (up to 39.6 t/ha) with resistance to viruses, common pathotype of cancer, golden potato nematode, common scab is presented in the article. It has a middle degree of resistance to late blight. A variety is of table appointment. A peel of tubers is white colour, pulp is light yellow, not darkening in a crude kind and at cooking, flowers it is red the violet. A bush is sprawling leafy type with large leaves; flowers are red-violet. Tubers of a new potato variety are suitable for processing on potato products: they have the oval form and superficial eyelets. The dry matter content is 20.2…27.9 %, protein - up to 2.4%, the average content of starch 12.4…16.2%. Taste qualities are 3.4…4.3 points; pulp of cooked tuber is light yellow fluffy. By results of competitive testing on experimental fields of Falenki Plant-Breeding Station in Kirovskoy area the variety Virazh exceeded the standard Nevsky on yield by 4.5 t/ha on average, variety Golubka by 2.1 t/ha. Under test digging at 60-th day after planing productivity of the new variety (10.6 t/ha) was higher then of the standard Nevsky and Golubka by 0.8 and 1.1 t/ha. The high yield is provided with the number tubers in the bush. A variety forms from 9 till 13 tubers per bush with average weight of the tuber 78…109 g. In 2015 variety Virazh is passed to the State variety trial.